The Evolution of BRAF Activation in Non-Small-Cell Lung Cancer - Zhang, Longyao; Zheng, Linpeng; Yang, Qiao; Sun, Jianguo (Frontiers in Oncology, 2022)
Non-small-cell lung cancer (NSCLC) is the most common subtype of lung cancer, of which approximate 4% had BRAF activation, with an option for targeted therapy. BRAF activation comprises of V600 and non-V600 mutations, fusion, rearrangement, in-frame deletions, insertions, and co-mutations. In addition, BRAF primary activation and secondary activation presents with different biological phenotypes, medical senses and subsequent treatments. BRAF primary activation plays a critical role in proliferation and metastasis as a driver gene of NSCLC, while secondary activation mediates acquired resistance to other targeted therapy, especially for epidermal growth factor tyrosine kinase inhibitor (EGFR-TKI). Treatment options for different activation of BRAF are diverse. Targeted therapy, especially two-drug combination therapy, is an important option. Besides, immune checkpoint inhibitors (ICIs) would be another option since BRAF activation would be a positive biomarker of tumour response of ICIs therapy. To date, no high level evidences support targeted therapy or immunotherapy as prioritized recommendation. After targeted therapy, the evolution of BRAF includes the activation of the upstream, downstream and bypass pathways of BRAF. In this review, therapeutic modalities and post-therapeutic evolutionary pathways of BRAF are discussed, and future research directions are also provided.